Використання технологій інтелектуального аналізу даних для підвищення ефективності прийняття лікарських рішень в кардіології - Якубовська, С. В. (ХНУРЕ, 2018)
The given work is devoted to the overall review of heart disease prediction using various data mining techniques. These techniques used in heart disease take less time and make process fast for the prediction system to predict heart disease with good accuracy in order to improve health. Data mining is the process of collecting large sets of data and then separating the meaning of data. Data mining provides the various techniques and methods for the transformation of data into useful information used for decision making in future.
Keywords: Data Mining; Knowledge base; Knowledge discovery; WizWhy